The Myth of Mosca: Instances of Antirealism in Eugenio Montale’s «Xenia» - Marco Tirrito (Humanities)
The objective of this essay is to demonstrate the fictional nature of the character Mosca in Xenia I and Xenia II, the first two sections of Eugenio Montale’s collection Satura (1971), and to illustrate the strategies through which the author makes this possible. Although Mosca is inspired by the historical figure of Drusilla Tanzi, the poet employs a series of macrotextual, thematic, linguistic, and rhetorical devices to elevate the female figure to that of a poetic character. The study briefly addresses these various devices and seeks to refute the hypothesis of a diary-like memorial structure in Xenia, advocating instead for a “narrative–novelistic” structure, which leverages the typical mechanisms of narrative fiction. The contribution demonstrates how the combination of these strategies significantly influences the character of Mosca, ultimately leading to her absorption within the fictional world of narrative poetry.